ANALYSIS OF KRAFT PAPER INSULATIONS LIFE FOR 15MVA POWER DISTRIBUTION TRANSFORMER IN TENAGA NASIONAL BERHAD - Sutan Chairul, Imran; Md Thayoob, Yasmin Hanum; Yang Ghazali, Young Zaidey; Ahmad Khiar, Mohd Shahril; Ab Ghani, Sharin (2012)
Among the most expensive and major equipment in any transmission and distribution electrical network is a transformer. Examples of electrical insulations for transformer are mineral oil and cellulose based paper. The said insulations degraded as transformers performed their work, while the most critical component of the transformer insulation system is the paper insulation. It is not easily replaced as compared to oil where it is easily reconditioned in-order to remove water and contaminants. Experimental and simulation studies on paper insulation showed that temperature, oxygen and moisture contents contributed to its degradation. Moisture and Furan were produced from these deterioration processes. In this study level of 2- Furaldehyde (2FAL) were obtained from Tenaga Nasional Berhad (TNB) in-service distribution power transformer. Categorizations were then carried out on these data for endof- life analysis. This study shows that the end-of-life in years derived from probability density function (Pdf)) can be used to estimate the life of paper insulation.